DII modulates the relationship between SVD3 and NAFLD prevalence, rather than liver fibrosis severity, in hospitalized T2DM population - Wei Xiang; Shi Cheng; Yuan Peng; Qiong Jin; Jun Yang (Scientific Reports)
Abstract Type 2 diabetes (T2DM) patients are at high risk for non-alcoholic fatty liver disease (NAFLD). Studies show SVD3 and dietary inflammatory index (DII) are associated with NAFLD. It’s unknown if they interact in T2DM patients with NAFLD. We collected data from 110 hospitalized T2DM patients, measured physiological and biochemical indicators, conducted dietary surveys, and converted data into DII and NFS, FIB-4, and BARD indices. We used logistic regression, mediation effect analysis, and moderation effect analysis to explore the relationship between DII and SVD3 with NAFLD and liver fibrosis in T2DM patients. DII was not significant in either NAFLD incidence in T2DM patients or liver fibrosis in NAFLD patients. SVD3 was positively correlated with NAFLD incidence in T2DM patients, but this correlation became insignificant as DII increased towards pro-inflammation. SVD3 is positively correlated with NAFLD incidence in T2DM patients, but this correlation becomes less significant as DII increases towards pro-inflammation.